EFEKTIVITAS PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 PADA MAHASISWA KEDOKTERAN ANGKATAN 2020 UNIVERSITAS NUSA CENDANA - Lian, Yohanis (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
The Covid-19 pandemic that occurred in Indonesia made the government issue a policy in the field of education, namely stopping face-to-face learning and establishing online learning. The role of educational institutions is very important in implementing online learning. Educational institutions are required to conduct effective online learning so that the learning process is successful. This research aims to see the extent to which online learning during the Covid-19 pandemic has been carried out effectively by looking at the achievement of learning objectives, the availability of learning facilities and infrastructure, the ability of lecturers and students to use technology, the efficiency of learning time, and the ability of online learning to replace face-to-face learning. for medical students batch 2020. This research uses a quantitative descriptive method in the form of a single variable. The data collection technique used a questionnaire instrument through the google form. The sample in this research was 67 active students of the medical faculty class of 2020 and took online learning. The results showed that the data obtained in this study was declared valid and reliable. Five indicators of effectiveness show that the percentage of each indicator is above 50%, where the condition for an indicator to be declared effective is to have a percentage above 50%. Thus, it can be concluded that online learning during the Covid-19 pandemic for medical students from the class of 2020 at Nusa Cendana University was declared effective. Although online learning is declared effective, as many as 65.7% of students prefer face-to-face learning.